MENGUAK RELASI PATRIOTISME, REVOLUSI DAN NEGARA DALAM FILM INDONESIA - Eka Nada Sofa Alkhajar (Jurnal Penelitian Humaniora, 2011)
The research aims to know how Pagar Kawat Berduri film describe about patriotism discourse, how the audiences interprete this film and what factors that make it produced by using critical discourse analaysis technique from Norman Fairclough model. This research uses qualitative approach with critical paradigm. Fairclough model analysis uses three dimensions as frame work: text, discourse practice (production and consumption) and socioculture practice. In text level, used semiotic analysis, then in discourse practice level, used documentary study and literature study to analize production matter and in other hand used indepth interview to analize consumption matter and also used documentary study and literature study for analizing in socioculture practice level. The research shows that Pagar Kawat Berduri film carried patriotism discourse in the scenes, attitudes, and dialogues by the actors. And also including the simbolizations that showed both from visual and picture languages: mimics, gestures, lighting, costumes etc. In the production side of discource practice level, the values of life from the director influenced very strong the film of Pagar Kawat Berduri. Then in the consumption side, audiences catch well about the messages in this film similar as that researcher had analized it in text analysis. At last in socioculture practice level, although Asrul Sani as the director gived great influence in his film but the authorize still limited by social structure where he lived. It’s means that the power of the state (government) in the era giving the greatest influence in this film because if there is a film didn’t match with the state (government) policy such as contributing in reinforced the revolution spirit, it will be band immediately